The Changes of Employment and Labor Productivity in South Sulawesi Province, Indonesia During The Covid-19 Pandemic - Widhatama, A.F. (EDP Sciences, 2023)
The Covid-19 pandemic has had a huge impact on various sectors, one of which is the employment sector in Indonesia. Through employment studies, it is hoped that it will be able to overcome employment problems which include labor absorption and labor productivity during the pandemic. This study is intended to determine labor absorption and labor productivity in South Sulawesi Province, especially during the Covid-19 pandemic by analyzing several indicators. Analysis of labor absorption is carried out based on main employment, employment by type, and employment status. This study uses a quantitative descriptive method by explaining changes in the dynamics of employment through absorption and labor productivity in South Sulawesi Province through BPS secondary data related to the state of the workforce in South Sulawesi Province. Quantitative analysis is used to measure labor productivity which is assessed through the elasticity of employment opportunities based on the type of business field. Through this study, a description of the absorption of labor in South Sulawesi Province showed that the Covid-19 pandemic had affected variations in the value of elasticity and absorption of labor in South Sulawesi Province. © 2023 EDP Sciences. All rights reserved.